Cultivar-specific response of bacterial community to cadmium contamination in the rhizosphere of rice (Oryza sativa L.). (October 2018) - Hou, Dandi; Wang, Runze; Gao, Xiaoyu; Wang, Kai; Lin, Zhi; Ge, Jun; Liu, Ting; Wei, Shuai; Chen, Weikang; Xie, Ruohan; Yang, Xiaoe; Lu, Lingli; et al.
Abstract: Cadmium accumulation in rice grains is highly dependent on its bioavailability that affected by various physicochemical properties and microbiological processes of soil. The rhizospheric bacterial communities of rice grown in contaminated soils by means of rice cultivars highly or weakly accumulating Cd in grains (HA and LA, respectively) were investigated. HA roots absorbed 7.26- and 2.25-fold more Cd than did LA roots at low (0.44 mg kg −1 ) and high (6.66 mg kg −1 ) soil Cd levels, respectively. Regardless of Cd levels, Cd bioavailability in the rhizosphere of HA was significantly higher than that of LA. Planting of rice and elevated Cd levels both significantly decreased bacterial α-diversity and altered bacterial community structure, with noticeable differences between the rice cultivars. Taxa specifically enriched in the HA rhizosphere (phyla Bacteroidetes, Firmicutes, and Deltaproteobacteria) can directly or indirectly participate in metal activation, whereas the LA rhizosphere was highly colonized by plant growth–promoting taxa (phyla Alphaproteobacteria and Gammaproteobacteria). The results indicate a potential association of Cd uptake and accumulation with rhizosphere bacteria in rice grown on a contaminated soil, thus providing baseline data and a new perspective on the maintenance of rice security. Graphical abstract: Highlights: Two rice cultivars (highly or weakly accumulating Cd in grains) had different rhizosphere metal bioavailabilities. Rice planting and elevated Cd levels decreased bacterial diversity and created specific rhizobacterial communities. Noticeable differences in compositions of key rhizobacterial taxa were found between two rice cultivars. Abstract : This study shows the cultivar-specific response of bacterial community to Cd contamination in rice rhizosphere and their potential role in rice Cd accumulation.